ACONTRIBUTION TO THE ANALYSIS OF SEMANTIC-DISCURSIVE STRATEGIES N THE TEXTUAL PRODUCTION OF STUDENTS AT AGOSTINHO NETO UNIVERSITY (PERcursos Linguísticos, 2025)
The development of a variety of Portuguese that is typical of Angola, with specific morphosyntactic, semantic-lexical and phonetic features, is now a widely recognised fact, both by speakers and by linguists and other specialists, to whom we owe the multiplicity of descriptive studies on this variety, many of which point to the need for its standardisation and made officialisation, in a context in which linguistic competence is measured according to the standard variety. This article aims to contribute to this reflection by addressing semantic-discursive aspects linked to this variety of Portuguese, analysing the choices in terms of discursive strategies used in ten texts produced in the classroom by students from the Faculty of Humanities at Agostinho Neto University, used as a sample. This research was carried out under the Systemic-Functional Grammar, by means of bibliographical and documentary research techniques, as we believe that this theory provides the necessary tools for analysing the logical-semantic and interdependent relationships on the basis of which texts are produced, determined by contextual factors. We hope, with the results of this study, to provide clues for a broader and more comprehensive description of the discursive strategies typical of students in this sociolinguistic context.